Sobolev space theory and Hölder estimates for the stochastic partial differential equations on conic and polygonal domains - Kim, Kyeong Hun; Lee, Kijung; Seo, Jinsol (Journal of Differential Equations, 2022)
We establish existence, uniqueness, and Sobolev and Hölder regularity results for the stochastic partial differential equation du=(∑i,j=1daijuxixj+f0+∑i=1dfxii)dt+∑k=1∞gkdwtk,t>0,x∈D given with non-zero initial data. Here {wtk:k=1,2,⋯} is a family of independent Wiener processes defined on a probability space (Ω,P), aij=aij(ω,t) are merely measurable functions on Ω×(0,∞), and D is either a polygonal domain in R2 or an arbitrary dimensional conic domain of the type [Formula presented] where M is an open subset of Sd−1 with C2 boundary. We measure the Sobolev and Hölder regularities of arbitrary order derivatives of the solution using a system of mixed weights consisting of appropriate powers of the distance to the vertices and of the distance to the boundary. The ranges of admissible powers of the distance to the vertices and to the boundary are sharp.
Keywords: Conic domains; Mixed weight; Parabolic equation; Weighted Sobolev regularity